2010
DOI: 10.1177/016146811011201409
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Approaches to Parent Engagement for Young English Language Learners and Their Families

Abstract: Parent involvement today is accepted in educational circles and across most communities as necessary for student success. Studies have shown that engaged and active parent involvement in the schooling of children heightens a sense of belonging and improves children's academic and behavioral performance. However, the literature also depicts that schools' conception, design, and implementation of parent involvement programs can defeat their purposes, as the traditional unidirectional program design disenfranchis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…However, many teachers are still not aware of alternatives to the “participation” model. Although many scholars have contended that teachers need to move beyond basic informational events—such as back-to-school nights, which are often rooted in deficit thinking (Chávez-Reyes 2010; García & Kleifgen, 2018; Lowenhaupt, 2014; Lowenhaupt & Montgomery, 2018; Lowenhaupt & Reeves 2017)—many teachers and schools need direction on how to effectively reach out to marginalized families and facilitate multicultural social activities and events in which multilingual families are valued for their linguistic and cultural resources (Brooks et al, 2021; Gándara et al, 2005; García & Kleifgen, 2018; Lopez et al, 2021). One way to do this is through providing PD on effective family engagement strategies.…”
Section: Literature Review: Engaging Multilingual/immigrant Familiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many teachers are still not aware of alternatives to the “participation” model. Although many scholars have contended that teachers need to move beyond basic informational events—such as back-to-school nights, which are often rooted in deficit thinking (Chávez-Reyes 2010; García & Kleifgen, 2018; Lowenhaupt, 2014; Lowenhaupt & Montgomery, 2018; Lowenhaupt & Reeves 2017)—many teachers and schools need direction on how to effectively reach out to marginalized families and facilitate multicultural social activities and events in which multilingual families are valued for their linguistic and cultural resources (Brooks et al, 2021; Gándara et al, 2005; García & Kleifgen, 2018; Lopez et al, 2021). One way to do this is through providing PD on effective family engagement strategies.…”
Section: Literature Review: Engaging Multilingual/immigrant Familiesmentioning
confidence: 99%
“…Removing barriers to access is often the first step in engaging multilingual families in meaningful ways. In her review of literature for working with families of young designated ELs, Chávez-Reyes (2010) argued that schools are responsible for creating environments that value and employ multiple languages, service-oriented leadership, and multicultural curricula. Research has shown that changing teachers’ perceptions of “access'' through PD, so that they more purposefully reach out to families, has improved multilingual family engagement (Lowenhaupt, 2014; Protacio et al, 2021).…”
Section: Literature Review: Engaging Multilingual/immigrant Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents and students require educational support that bridges linguistic and cultural gaps to navigate the educational pipeline (Chavez-Reyes, 2010; Lawson & Alameda-Lawson, 2012). Engaged parents can increase a community sense of educational belonging, helping to improve student educational outcomes (Cammarota, 2006; Chavez-Reyes, 2010; Jasis & Ordoñez-Jasis, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Parents and students require educational support that bridges linguistic and cultural gaps to navigate the educational pipeline (Chavez-Reyes, 2010; Lawson & Alameda-Lawson, 2012). Engaged parents can increase a community sense of educational belonging, helping to improve student educational outcomes (Cammarota, 2006; Chavez-Reyes, 2010; Jasis & Ordoñez-Jasis, 2012). School and districts, however, require the necessary resources to engage in supportive school improvement plans that include linguistically and culturally relevant communication from the institution of education to the community, and, by proxy, to the parents (Betters-Bubon & Schultz, 2017; Jasis & Ordoñez-Jasis, 2012; Ramirez, 2010).…”
Section: Discussionmentioning
confidence: 99%